OP VI – 2 Organ-specific integrative exposure assessment for radio-frequency electromagnetic fields: general population exposure and dose contribution of various sources. (18th March 2018) - Wel, Luuk van; Liorni, Ilaria; Capstick, Myles; Thielens, Arno; Aerts, Sam; Joseph, Wout; Wiart, Joe; Cardis, Elisabeth; Vermeulen, Roel
Abstract : Background/aim: The daily dose of radio-frequency electromagnetic fields (RF-EMF) received by the human body depends on source, use, and body characteristics. We developed a model capable of estimating total RF-EMF dose (J/kg) for 64 body tissues as well as the contribution of specific sources to total dose based on personal characteristics, source characteristics, and scenarios of use. Methods: The Integrated Exposure Model (IEM) uses personal characteristics and scenarios of use to estimate daily RF-EMF dose from mobile phones, DECT phones, tablets, body area networks, laptops, on/near body devices, smartwatches, virtual reality headsets, WiFi routers, and far field sources. Specific absorption rates (SAR) in various tissues were calculated for each source using transfer algorithms based on source and body characteristics. These were then adjusted for scenarios of use. Lastly, the model calculated the integrative dose from all sources combined and the relative contribution of each source. To estimate population exposure levels, we used data from an online survey on use of mobile communication devices deployed in four countries (France, the Netherlands, Spain, Switzerland). Results: The online survey resulted in a dataset of 1768 participants, with a mean age of 52 years. Preliminary results indicate an average whole body dose of 0.15 J/kg per day, and an average whole brain dose of 0.09 J/kg per day. Women tended to have slightly higher doses than men, particularly in the youngest age group, due to higher reported use of mobile phones for voice and data. Source specific contribution varied depending on tissue. For the brain, the highest contribution (32%) came from mobile phones. Phone, tablet, and WiFi use together account for 91% of total brain dose. For the whole body: phone data use, WiFi, tablet, and laptop use accounted for 97% of the average total dose in our population. Conclusion: We developed a model capable of estimating integrative RF-EMF dose from both current and novel devices. Using survey data on device use we were able to estimate average whole brain (0.09 J/kg) and average whole body (0.15 J/kg) dose. Device output powers in various scenarios of use were found to strongly influence model results.